A modular variable-process treatment system for operation liquid waste: A case study. (June 2020) - Wang, Yong; Wang, Xiaochang C.; Jin, Xin; Wang, Rui; Shi, Xuan; Jin, Pengkang; Yu, Ya
Highlights: The types and composition of OLW with variable water quality were characterized. OLW was divided into three categories using a water quality matrix. A modular variable-process treatment system is proposed. The quality of the effluent meets the reinjection requirements (SY/T 5329-2012). Abstract: The components of petroleum wastewater are complex and variable, which makes it hard to meet the reinjection requirements based on a fixed treatment process. Therefore, an efficient wastewater treatment system adapting to variable water quality is necessary. In this study, the types and composition of wastewater from the Changqing oilfield were systematically analyzed. The characteristics of different types of wastewater were clustered by a water quality matrix. Based on the results, viscosity is an important limiting factor in wastewater treatment. Six types of wastewater could be divided into high contaminative wastewater (HCW), medium contaminative wastewater (MCW) and low contaminative wastewater (LCW). Thus, a modular and variable-process wastewater treatment system was developed. The system consists of five modular units including oil removal, viscosity reduction, DAF/DOF, two-stage filtration, and ultraviolet disinfection. Each module can be flexibly used for the wastewater treatment according to the variable water quality and characteristics of raw water. The system was stable and reliable during 160 days of field operation. The suspended solids (SS), petroleum concentration, and median particle size of treated wastewater were less than 2.0 mg/L, 6.0 mg/L and 1.5 μm, respectively, which meet the requirements of the reinjection standard. The treatment system can improve the wastewater treatment efficiency with variable water quality in the oilfields and protect regional environmental safety.